Conducting Functional Communication Training via Telehealth to Reduce the Problem Behavior of Young Children with Autism - Wacker, David P. (2012)
Functional communication training (FCT) was conducted by parents of 17 young children with autism spectrum disorders who displayed problem behavior. All procedures were conducted at regional clinics located an average of 15 miles from the families’ homes. Parents received coaching via telehealth from behavior consultants who were located an average of 222 miles from the regional clinics. Parents first conducted functional analyses with telehealth consultation (Wacker, Lee, et al., in press) and then conducted FCT that was matched to the identified function of problem behavior. Parent assistants located at the regional clinics received brief training in the procedures and supported the families during the clinic visits. FCT, conducted within a nonconcurrent multiple baseline design, reduced problem behavior by an average of 93.5%. Results suggested that FCT can be conducted by parents via telehealth when experienced applied behavior analysts provide consultation.